2022
DOI: 10.1007/s10597-022-00963-5
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the ‘Crisis Toolbox’: a skills-based intervention delivered in a Crisis Resolution and Home Treatment Team during COVID-19

Abstract: Crisis Resolution and Home Treatment Teams (CRHTTs) provide 24-hour, seven day per week support for people in crisis. The COVID-19 pandemic has placed significant demand on urgent care and increased the need for brief interventions in CRHTT settings with flexible methods of delivery. This evaluation aimed to examine client satisfaction with the ‘Crisis Toolbox’ (CTB), a brief, skills-based intervention delivered in one CRHTT during COVID-19. All participants who received the CTB completed a satisfaction questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Changes in PHQ-9 and GAD-7 scores could be due to several factors including natural variation, regression to the mean, situational factors, the Hawthorne effect, treatment as usual (including the effect of crisis safety planning), or the psychological components of frequent contacts (McCabe et al, 2018 ). Although it is likely the CTB has some effect, especially considering its high acceptability (Mulligan et al, 2022 ), more rigorous studies employing control groups and trial methodology are required to determine this. Secondly, the retrospective nature of this evaluation meant that demographic, clinical and outcome variables were restricted to those previously recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in PHQ-9 and GAD-7 scores could be due to several factors including natural variation, regression to the mean, situational factors, the Hawthorne effect, treatment as usual (including the effect of crisis safety planning), or the psychological components of frequent contacts (McCabe et al, 2018 ). Although it is likely the CTB has some effect, especially considering its high acceptability (Mulligan et al, 2022 ), more rigorous studies employing control groups and trial methodology are required to determine this. Secondly, the retrospective nature of this evaluation meant that demographic, clinical and outcome variables were restricted to those previously recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of these skills was manualised, formulation driven (i.e., selected based on the needs of each individual service user) and flexible (i.e., delivered either face-to-face or via telephone), and were used to supplement crisis safety planning delivered by members of the wider CRHTT. The CTB has been previously shown to have high acceptability for those experiencing mental health crises (Mulligan et al, 2022 ). However, it remains unknown if the CTB has a positive effect on psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 91 studies, 18 were removed because they were literature reviews, conference proceedings, commentary, instructional materials, or guidelines, 6o were removed after the title and abstract screening, and one was removed after reviewing the content. Twelve studies reported the risk management support to home-based community care staff during the COVID-19 pandemic, including six studies with qualitative feedback ( 20 25 ), four studies with quantitative feedback ( 26 29 ) and two studies with mixed method ( 30 , 31 ). Of these, three studies reported limited access to personal protective equipment (PPE) for home care staff and their service users in the early phase of COVID-19 and unclear guidelines on infection control ( 26 , 27 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies ( 22 25 , 29 ) reported telemedicine as one of the strategies for maintaining the home-based primary care service and its challenges, such as technical difficulties in approaching patients amidst the pandemic. Researchers also stated how community health workers adjusted the services to meet their needs, such as arranging case management outreach, coordinating elderly services and providing assistance to secure the basic needs of their home-based community care services ( 20 , 21 , 28 , 30 , 31 ). Mulligan et al ( 31 ) evaluated the client satisfaction with mental health interventions, such as stress management, sleep hygiene etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation